La educación italiana en La Plata durante el fresquismo (provincia de Buenos Aires, Argentina, 1936-1940) - Bruno Cimatti (Confluenze)
Between 1936 and 1940, the administration of the openly philo-fascist Manuel Antonio Fresco as the governor of the province of Buenos Aires involved deep transformations in the practices and discourses that shaped the governance of Argentina's first province. Italian education in La Plata, the province’s capital, was not exempt from this process. This article explores the trajectory of the Società di Cultura Italica “Vittorio Emanuele III” in La Plata, dedicated to children and youth, during the period of ideological alignment with Fresco’s government – a period not devoid of tensions.